2019–2020 Florida Citrus Production Guide: Citrus Black Spot - Megan M. Dewdney; Timothy S. Schubert; Mark R. Estes; Pamela D. Roberts; Natalia A. Peres (EDIS)
Citrus black spot is caused by the fungus Phyllosticta citricarpa (formerly Guignardia citricarpa). The disease causes fruit blemishes and significant yield losses, especially on sweet oranges. Black spot can affect all commercial citrus species and cultivars commonly grown in Florida. This 8-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by  M. M. Dewdney, T. S. Schubert, M. R. Estes, P. D. Roberts, and N. A. Peres, and published by the Plant Pathology Department, March 2019.